The Development of Audio Visual Learning Media Based on Genius Learning in Exposition Text Learning by Grade X SMK Tritech Informatika Medan - Ardina Ardina; Abdurahman Adisaputera; Sumarsih Sumarsih (BIRCU, 2020)
This study aims to determine: (1) Describe the audio visual learning media based on genius learning which is effective for class X students of SMK Tritech Informatika Medan, (2) Describe the results of the development carried out on genius learning-based audio visual media for class X SMK Tritech Informatika students. Medan, (3) Describe the reasons for using audio-visual learning media based on genius learning in developing exposition text learning media. This research is a development research using the Borg & Gall model which aims to develop an audio-visual learning media based on genius learning that will be used as an exposition text learning medium. This learning media will be tested from material experts, design experts, media experts, Indonesian language teachers, and students of SMK Tritech Informatika Medan, consisting of 3 students in individual trials, 9 students in small group trials, and 25 students in field trials. The instrument used in this study was a questionnaire. (1) The results of validation by material experts with an average of 79% with good criteria, (2) validation results by media experts with an average of 80% with good criteria, (3) validation by instructional media design experts with an average of 82 % with very good criteria, (4) the response of Indonesian language teachers with an average of 86% with very good criteria, (5) the acquisition of individual trial results with an average of 78.5% with good criteria, (6) The acquisition of trial results small group with an average of 79% with good criteria, (7) Acquisition of field trial results with an average of 83.54% with very good criteria, (8) Student learning outcomes before using audio-visual learning media based on genius learning were 66.2 and after using audio-visual learning media based on genius learning with an average score of 78 in the good category. The difference obtained is 11.8. This proves that the genius learning-based audio-visual learning media developed can improve student learning outcomes, thus, this genius-based audio-visual learning media is effectively used in learning exposition text.